Clear Cell Myoepithelial Carcinoma of Salivary Glands Showing EWSR1 Rearrangement: Molecular Analysis of 94 Salivary Gland Carcinomas With Prominent Clear Cell Component. (March 2015) - Skálová, Alena; Weinreb, Ilan; Hyrcza, Martin; Simpson, Roderick H.W.; Laco, Jan; Agaimy, Abbas; Vazmitel, Marina; Majewska, Hanna; Vanecek, Tomas; Talarčik, Peter; Manajlovic, Spomenka; Losito, Simona N.; et al.
Abstract : This study examines the presence of the EWSR1 rearrangement in a variety of clear cell salivary gland carcinomas with myoepithelial differentiation. A total of 94 salivary gland carcinomas with a prominent clear cell component included 51 cases of clear cell myoepithelial carcinomas de novo (CCMC), 21 cases of CCMCs ex pleomorphic adenoma (CCMCexPA), 11 cases of epithelial-myoepithelial carcinoma (EMC), 6 cases of EMC with solid clear cell overgrowth, and 5 cases of hyalinizing clear cell carcinoma of minor salivary glands. In addition, 10 cases of myoepithelial carcinomas devoid of clear cell change and 12 cases of benign myoepithelioma were included as well. All the tumors in this spectrum were reviewed, reclassified, and tested by fluorescence in situ hybridization (FISH) for the EWSR1 rearrangement using the Probe Vysis EWSR1 Break Apart FISH Probe Kit. The EWSR1 rearrangement was detected in 20 of 51 (39%) cases of CCMC, in 5 of 21 (24%) cases of CCMCexPA, in 1 of 11 (9%) cases of EMC, and in 4 of 5 (80%) cases of hyalinizing clear cell carcinoma. The 25 EWSR1 -rearranged CCMCs and CCMCexPAs shared similar histomorphology. They were arranged in nodules composed of compact nests of large polyhedral cells with abundant clear cytoplasm. Necrosis, areas of squamous metaplasia, and hyalinization were frequent features. Immunohistochemically, the tumors expressed p63 (96%), cytokeratin CK14 (96%), and S100 protein (88%). MIB1 index varied from 10% to 100%, with most cases in the 20% to 40% range. Clinical follow-up information was available in 21 cases (84%) and ranged from 3 months to 15 years (mean 5.2 y); 4 patients were lost to follow-up. Ten patients are alive with no evidence of recurrent or metastatic disease in the follow-up period from 3 months to 15 years (mean 5 y), 3 patients are alive with recurrent and metastatic disease, and 8 died of disseminated cancer 9 months to 16 years after diagnosis (mean 6 y). Lymph node metastasis appeared in 5 patients within 5 months to 4 years after diagnosis (mean 22 mo), distant metastases were noted in 7 patients with invasion of orbit (2 cases), and in 1 case each metastasis to the neck soft tissues, liver, lungs, mediastinum, and thoracic vertebra was noted. We describe for the first time EWSR1 gene rearrangement in a subset of myoepithelial carcinomas arising in minor and major salivary glands. The EWSR1 -rearranged CCMC represents a distinctive aggressive variant composed predominantly of clear cells with frequent necrosis. Most EWSR1 -rearranged CCMCs of salivary glands are characterized by poor clinical outcomes.